PERANAN KAMPUS DALAM PROGRAM TANGGAP DARURAT BENCANA ALAM SEROJA DI NUSA TENGGARA TIMUR - Fransiska Widyawati (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
In the first week of April 2021, Tropical Storm Seroja hit NTT Province and caused a hydrometeorological disaster. The most affected areas are East Flores, Adonara, Malacca, Kupang. The losses caused by the disaster were enormous. Therefore, assistance from various parties is needed to be able to overcome and handle the disasters. The Indonesian Catholic University of Santu Paulus Ruteng, located in this province, was called to take action for disaster emergency response. This article describes the work of community service. The method used is disaster response which is carried out in several stages namely: initial initiative, the establishment of emergency response posts, fundraising, identification of victims' needs, delivery of assistance, and public accountability reports. This activity collaborates with internal campus teams: leaders, lecturers, students and external campuses such as alumni and partners. The result of this activity is that many disaster victims have received relief and assistance. In conclusion, Community Service has a positive impact on handling the Seroja disaster in Flores, East Nusa Tenggara